Inisiatif Bela Negara di Instagram Untuk Generasi Z: Membangun Patriotisme Melalui Media Sosial - Maharani Al Faruq, Aulia Azizah; Fakhiroh, Lia; Dewi, Ira Kristina; Mandasari, Diniati Kurnia Wahyu; Maulana, Alzena Ahnaf; Azhar, Chintya Dwi; Darmawan, Muhammad Hafiz Alif; Bhaskara, Ferdian Aji; Ningrum, Reza Setya; Ramadhan, Ridho; Susanto, Tantut (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Social media has become the main platform for Generation Z, but utilization to instill state defense values is still not optimal. This study aims to analyze the effectiveness of using Instagram social media in conveying the values of state defense and the formation of patriotism attitudes in Generation Z. Using a descriptive media approach with a social campaign method through digital media, conducted by ten student members. Data collection was carried out through descriptive observations of Instagram content that received interaction with the patriotism message conveyed. The highest results were found in the content with the theme of patriotism with the title “Bung Tomo: The Spirit of Arek-Arek Surabaya!”. The content managed to get 287 likes and 46 comments, with comments that were generally positive. This study concludes that Instagram can be an effective medium to instill national defense values in Generation Z when the content is tailored to the characteristics and preferences of the generation. It is recommended that we are encouraged to optimize the use of Instagram in national defense campaigns and patriotism with a more interactive content strategy that is relevant to Generation Z.